(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The research focused on promoting community sustainability and highlighting its role in achieving sustainable development through solar energy, especially since it is considered one of the most important renewable energy sources. Its use reduces gas emissions, carbon waste, and noise, thereby mitigating the impact of climate change. The research question emphasizes that despite the presence of traditional energy sources in Iraq, particularly crude oil and natural gas, these resources are depleted and not renewable. However, their continued use poses a risk of environmental pollution and injustice to future generations. It also focused on reviewing previous studies on the concepts of social sustainability as a starting point for achieving sustainable development goals (the theoretical aspect). It also collected data on the costs of installing and maintaining solar energy systems, as well as monthly and annual consumption calculations for a number of homes. It also selected an agricultural model (irrigation system). It also evaluated the feasibility of investing in solar energy systems over a 10-year period compared to consumption using conventional sources. The research answered the question: What is the relationship between social sustainability and the application of solar energy systems in achieving sustainable development goals? What are the challenges and opportunities facing this relationship in this context? The research reached several conclusions, including: Enhancing community empowerment, which has positive impacts at the local level, such as job creation. Enhancing the environmental aspect and environmental sustainability, such as reducing emissions and increasing shaded areas, which reduces temperatures above homes, albeit relatively. Among the challenges facing solar energy projects are the lack of funding and a lack of awareness among individuals. This research is within the general framework and can be modified to suit the circumstances and level of use. With the assistance of specialists in this field, the design and engineering aspects are detailed and precise, according to the needs of the community. With the situation as mentioned above.